2020
DOI: 10.1371/journal.pbio.3000622
|View full text |Cite
|
Sign up to set email alerts
|

Eating breakfast and avoiding late-evening snacking sustains lipid oxidation

Abstract: Circadian (daily) regulation of metabolic pathways implies that food may be metabolized differentially over the daily cycle. To test that hypothesis, we monitored the metabolism of older subjects in a whole-room respiratory chamber over two separate 56-h sessions in a random crossover design. In one session, one of the 3 daily meals was presented as breakfast, whereas in the other session, a nutritionally equivalent meal was presented as a lateevening snack. The duration of the overnight fast was the same for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
3
39
1
Order By: Relevance
“…In addition, misalignment of endogenous and exogenous cycles, for example during shift work, promotes the development of metabolic morbidities 176 . Recently, it has been demonstrated that, besides lunch and dinner, an additional meal in the late evening, rather than in the morning, attenuates overnight lipid catabolism, 178 potentially counteracting weight loss. In mice, pathological consequences of high‐fat diet, that ismetabolic disruption and obesity, depend on the time of food intake rather than calories consumed 179‐181 …”
Section: Modern Life Challenges To the Human Circadian Systemmentioning
confidence: 99%
“…In addition, misalignment of endogenous and exogenous cycles, for example during shift work, promotes the development of metabolic morbidities 176 . Recently, it has been demonstrated that, besides lunch and dinner, an additional meal in the late evening, rather than in the morning, attenuates overnight lipid catabolism, 178 potentially counteracting weight loss. In mice, pathological consequences of high‐fat diet, that ismetabolic disruption and obesity, depend on the time of food intake rather than calories consumed 179‐181 …”
Section: Modern Life Challenges To the Human Circadian Systemmentioning
confidence: 99%
“…Fatty acids are the main energy source during overnight fasting [35,36]. There is evidence that individuals who engage in night eating have decreased fat oxidation [37][38][39]. Although fat oxidation was found to be downregulated among obese individuals [40] and those who are prone to obesity [41], little is known about whether there is downregulation of fat oxidation during pregnancy, which could contribute to hunger at night.…”
Section: Potential Reasons For Maternal Night Eatingmentioning
confidence: 99%
“…Chronopharmacology that takes into account circadian pharmacokinetics and pharmacodynamics already plays an important role for a number of medications widely used for treating oncological, metabolic, and respiratory diseases [433,434]. Additionally, the rapidly developing field of chrononutrition emphasizes the importance of meal timing for prevention and treatment of metabolic diseases [432,[435][436][437] (for review, see Ref. [438]).…”
Section: Perspectivesmentioning
confidence: 99%